2007
DOI: 10.1093/pasj/59.sp3.s785
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Sheared Magnetic Fields of Two X-Class Flares Observed by Hinode/XRT

Abstract: We present multi-wavelength observations of the evolution of the sheared magnetic fields in NOAA Active Region 10930, where two X-class flares occurred on 2006 December 13 and December 14, respectively. Observations made with the X-ray Telescope (XRT) and the Solar Optical Telescope (SOT) aboard Hinode suggest that the gradual formation of the sheared magnetic fields in this active region is caused by the rotation and west-to-east motion of an emerging sunspot. In the pre-flare phase of the two flares, XRT sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…In Figure 8(a) we have densely traced these highly heated field lines, whose temperature has reached about 10 MK. The heated sigmoid-shaped core field may give rise to the bright sigmoid loops in the pre-eruption region observed in Hinode XRT images (Figure 8(b), also Su et al 2007, see their Figure 1). …”
Section: Onset Of the Eruptionmentioning
confidence: 91%
“…In Figure 8(a) we have densely traced these highly heated field lines, whose temperature has reached about 10 MK. The heated sigmoid-shaped core field may give rise to the bright sigmoid loops in the pre-eruption region observed in Hinode XRT images (Figure 8(b), also Su et al 2007, see their Figure 1). …”
Section: Onset Of the Eruptionmentioning
confidence: 91%
“…[20] The active region NOAA 10930 is well known for the X3.4 class flare on 13 December 2006, which was captured by Hinode satellite soon after its launch, and has been carefully studied by many authors [e.g., Zhang et al, 2007;Moon et al, 2007;Kubo et al, 2007;Su et al, 2007;Yan et al, 2007;Schrijver et al, 2008;Jing et al, 2008;Guo et al, 2008;Su et al, 2008;Wang et al, 2008;Tan et al, 2009;Yan et al, 2009;Magara, 2009;Min and Chae, 2009;Li and Zhang, 2009;Jing et al, 2010]. Dozens of vector magneto-grams of NOAA 10930 were obtained by Hinode/SOT-SP when the active region crossed the Sun's disk during the first half of December 2006 [Matsuzaki et al, 2007].…”
Section: Sot-sp Photospheric Vector Magnetogramsmentioning
confidence: 99%
“…In the latter case, flare loops typically form at higher altitude as time passes by, as the energy release site moves upward (Liu et al 2004;Warren et al 2011). Time sequences of flares also indicate that flare loops formed at the beginning of the flare have a more pronounced shear, evidenced by comparing their direction with that of the local polarity inversion line (PIL), than those formed later (Asai et al 2003;Su et al 2007). In Aulanier et al (2012), the authors investigated the evolution of the shear from strong values to weak ones by comparing observations with a numerical model, and showed that coronal loops reconnecting later in time were also closer to potential loops, due to their initial low shear as well as to the dynamics of the ejected flux rope that decreases the shear of reconnecting field lines (see figure 16 which illustrates this dynamics).…”
Section: Flare Loops and Flux Ropementioning
confidence: 99%